Pengaruh Upah Minimum terhadap Ketimpangan dan Kemiskinan di Pulau Jawa - Haerunisa, Ia; Eka Nabila, Asyifa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Income inequality and poverty continue to be major challenges in Indonesia's industrial areas, especially in DKI Jakarta, West Java, and Banten, although minimum wage policies continue to be developed as a form of protection for low-income workers. These policies theoretically serve as an instrument for income redistribution and improvement of labor welfare, but their effectiveness in reducing inequality and reducing poverty rates is still questionable, especially in areas with highly industrialized economic structures. This study aims to analyze the influence of income inequality, poverty rate, economic growth, and unemployment rate on the dynamics of the provincial minimum wage in the 2016–2023 period. The study used secondary data obtained from the Central Statistics Agency and analyzed using panel data regression to obtain a comprehensive empirical picture of the factors determining the minimum wage. The test results show that the Fixed Effect Model is the most suitable model for capturing variations between provinces and between times. Key findings reveal that poverty levels and economic growth have a significant influence on changes in the minimum wage, while income inequality and unemployment rates have no significant influence. The conclusion of the study emphasizes that the minimum wage policy is not effective enough in reducing income inequality and reducing poverty without the expansion of the formal sector, improving the quality of the workforce, and distributing economic growth more evenly between industrial areas.